2014
DOI: 10.1007/s00590-014-1559-0
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical relations of anterior and posterior ankle arthroscopy portals: a cadaveric study

Abstract: This study provides information on the anatomical relations of ankle arthroscopy portals and relevant neurovascular structures, confirming previous studies identifying the superficial peroneal nerve as the structure at highest risk of injury, but also highlighting some important variations. Techniques to minimise the injury to these structures are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A comparison between the results of the current study and previous reports on the safety of arthroscopy of the ankle shows substantial variability. For example, where this study found an average distance of 6.8‐mm between the anteromedial portal and the great saphenous vein, previous studies reported distances of 5.4‐mm [18], 9.0‐mm [4], and 10.7‐mm [13]. Whilst this and previous studies do provide a general idea of which portals can safely be used for arthroscopy, the variability in anatomic distributions underscores the need for careful introduction of arthroscopic portals.…”
Section: Discussionmentioning
confidence: 77%
“…A comparison between the results of the current study and previous reports on the safety of arthroscopy of the ankle shows substantial variability. For example, where this study found an average distance of 6.8‐mm between the anteromedial portal and the great saphenous vein, previous studies reported distances of 5.4‐mm [18], 9.0‐mm [4], and 10.7‐mm [13]. Whilst this and previous studies do provide a general idea of which portals can safely be used for arthroscopy, the variability in anatomic distributions underscores the need for careful introduction of arthroscopic portals.…”
Section: Discussionmentioning
confidence: 77%
“…The structure at highest risk of injury is the IDCN, and clinical studies have frequently reported injury to the SPN or its branches when using the anterolateral portal. 11 Ferkel et al. 2 also reported an overall complication rate of 9% in 612 ankle arthroscopies, with the most common complication being neurologic injury, which accounted for 49% of the complications.…”
Section: Discussionmentioning
confidence: 98%
“…To avoid these complications, several methods to establish portals, such as use of a mosquito clamp after skin incision, a nerve palpation technique, and a transillumination technique, have been suggested. 1 , 2 , 11 , 13 , 14 However, to reduce the risk of iatrogenic injury to the nerve, it is expected that our method will identify neurovascular structures more easily before making arthroscopic portal incisions. Ferkel et al.…”
Section: Discussionmentioning
confidence: 99%
“…Oliva et al reported that the intermediate dorsal cutaneous nerve was the structure most likely to be injured by the anterolateral portal [11]. Another study reported that SPN, namely, the intermediate dorsal cutaneous nerve and the medial dorsal cutaneous nerve, is one of the most common complications, accounting for up to 50% of the cases [6].…”
Section: Discussionmentioning
confidence: 99%